Getting Out of the Black Box: analogising the use of computers in electronic music and sound art. - Charrieras, Damien; Mouillot, François (Organised Sound, 2015)
The process of creating computer-based music is increasingly being conceived in terms of complex chains of mediations involving composer/performer and computer software interactions that prompt us to reconsider notions of materiality within the context of digital cultures. Recent scholarship has offered particularly useful re-evaluations of computer music software in relation to musical instrumentality. In this article, we contend that given the ubiquitous presence of computer units within contemporary musical practices, it is not simply music software that needs to be reframed as musical instruments, but rather the diverse material strata of machines identified as computers that need to be thought of as instruments within music environments. Specifically, we argue that computers, regardless of their technical specifications, are not only ‘black boxes’ or ‘meta-tools’ that serve to control music software, but are also material objects that are increasingly being used in a wide range of musical and sound art practices according to an ‘analog’ rather than ‘digital’ logic. Through a series of examples implicating both soft and hard dimensions of what constitutes computers, we provide a preliminary survey of practices calling for the need to rethink the conceptual divide between analog and digital forms of creativity and aesthetics.